2022
DOI: 10.1002/adma.202205338
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Triggered Sustainable Defect‐Passivation for Stable Perovskite Photovoltaics

Abstract: The generation of photoinduced defects and freely moving halogen ions is dynamically updated in real time. Accordingly, most reported strategies are static and short‐term, which make their improvements in photostability very limited. Therefore, seeking new passivation strategies to match the dynamic characteristics of defect generation is very urgent. Without newly generated defects, a passivation molecule should exist in the configuration that would not become the initiation sites for defect generation. With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…105 DAE (C 18 H 19 NO 2 S 2 ), through molecular isomerism, can repeatedly invert between open and closed-ring isomers, reaching kinetic equilibrium states (state I and state II) via absorbing UV (365 nm) and visible light (>500 nm), and sustaining UV on/off cycling in the precursor solution, and thus, it is capable of providing long-term light stable and sustainable UV protection to devices. 105 Later, Wang et al 106 developed a sustainable dynamic passivation method for PSCs by adopting the photoisomeric molecule spiropyran. Our group 107 monitored the reversible phase-transition process of FA-dominated perovskites, namely δ-to-α phase (heat healing) and α-to-δ phase (humidity aging).…”
Section: Reducing Corrosion Sites To Improve the Stability Of Perovsk...mentioning
confidence: 99%
“…105 DAE (C 18 H 19 NO 2 S 2 ), through molecular isomerism, can repeatedly invert between open and closed-ring isomers, reaching kinetic equilibrium states (state I and state II) via absorbing UV (365 nm) and visible light (>500 nm), and sustaining UV on/off cycling in the precursor solution, and thus, it is capable of providing long-term light stable and sustainable UV protection to devices. 105 Later, Wang et al 106 developed a sustainable dynamic passivation method for PSCs by adopting the photoisomeric molecule spiropyran. Our group 107 monitored the reversible phase-transition process of FA-dominated perovskites, namely δ-to-α phase (heat healing) and α-to-δ phase (humidity aging).…”
Section: Reducing Corrosion Sites To Improve the Stability Of Perovsk...mentioning
confidence: 99%
“…41 In particular, metal/organic halide salt additives such as NaX, CsX, KX, RbX, MAX, and FAX (where X = F, Cl, Br) have been added in to the precursor solution and/or the lattice of halide perovskites, showing two main functions: (1) cations with a suitable radius can occupy the A-site to stabilize the perovskite structure and adjust its band gaps and photoelectric properties and (2) anions anchor Pb 2+ through hydrogen bonds to inhibit the movement and immigration of Pb 2+ cations. 42 On the other hand, the surface modification of perovskite films aims to passivate grain boundaries and/or surface defects, forming a protective layer and constructing well-matched energy levels for PSCs. 43,44 It should be noted that most of the used additives and surface modifiers are sacrificial agents nowadays, which are not able to continuously passivate the newly formed defects during the operation of PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Several sustainably utilized agents have attracted significant attention for removing the regenerated defects, which would be beneficial for promoting the lifetimes of PSCs. 42,45,46 For instance, Shi et al introduced spiropyran molecules as a capping layer on the perovskite film, which incessantly passivated the renewable Pb vacancies in FAPbI 3 -based PSCs, leading to much improved PCEs and long-term stability under sunlight illumination. 42 In another work, Wang et al reported that the Eu 3+ /Eu 2+ redox pair could continuously oxidize Pb 0 and reduce I 0 defects circularly in FAPbI 3 -based PSCs to achieve enhanced PCEs and operational durability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shi et al reported that the transition between the pre- and post-isomeric forms could dynamically capture continuous renewal of defects, thus realizing continuous defect repair. 16 Kim et al reported a dual-side modification layer, poly-BCP, between the electron transport layer and PVK layer. The polymerized alkyl chain bridges could enable a uniform film structure and thus result in excellent transport characteristics.…”
Section: Introductionmentioning
confidence: 99%